Determination and Confirmation of Nicarbazin, Measured as 4, 4-Dinitrocarbanilide (DNC), in Chicken Tissues by Liquid Chromatography with Tandem Mass Spectrometry: First Action 2013.07. (27th November 2019) - Coleman, Mark R; Rodewald, John M; Brunelle, Sharon L; Nelson, Maria; Bailey, Lauryn; Burnett, Thomas J
Abstract: A single-laboratory validation (SLV) study was conducted on an LC/MS/MS method for the determination and confirmation of nicarbazin, expressed as 4, 4-dinitrocarbanilide (DNC), in chicken tissues, including liver, kidney, muscle, skin with adhering fat, and eggs. Linearity was demonstrated with DNC standard curve solutions using a weighted (1/x) regression and confirmed with matrix-matched standards. Intertrial repeatability precision (relative standard deviation of repeatability; RSDr ) was from 2.5 to 11.3%, as determined in fortified tissues. The precision was verified with incurred tissue, and varied from 0.53 to 2.5%. Average recoveries ranged from 82% in egg to 98% in kidney. Although the average recoveries across all concentrations were within the acceptable range, the method was improved with the inclusion of an internal standard and the use of matrix-matched standards. Accuracy for the improved method in chicken liver varied from 93 to 99% across all concentrations (100–8000 ng/g) compared to recoveries below 80% at concentrations between 100–400 ng/g in chicken liver for the original method. The limit of detection was estimated to be less than 3.0 ng/g in all tissue types, and the limit of quantitation was validated at 20 ng/g. Based on confirmatory ion ratios and peak retention times, the false-negative rate was estimated as 0.00% (95% confidence limits 0.00, 0.74%) from 484 fortified samples and 12 incurred residue samples analyzed using the U.S. and EU confirmation criteria. Small variations to the method parameters, with the exception of injection volume, did not have a significant effect on recoveries. Stability was determined for fortified tissues, extracts, and standard curve solutions. The data collected in this study satisfy the requirements of SLV studies established by the AOAC Stakeholder Panel for Veterinary Drug Residue and the method was awarded First Action Official Method SM status by the Expert Review Panel for Veterinary Drug Residues on May 7, 2013.